Shari’ah committee composition in Malaysian Islamic Financial Institutions: Post implementation of SGF 2010 and IFSA 2013 - Ismail, Muhammad Issyam; Hassan, Rusni (IIUM Press, 2016)
Shari’ah Governance is what makes Islamic Financial Institution (IFI) different from the Conventional Financial Institution. The primary aim of Shariah Governance is to ensure that the operation, practice, instrument, product and management of the IFIs are compliant with the Shari’ah principles at all times. The Shari’ah Governance framework has been outlined in several standard and guideline issued by various bodies and organizations. At the global level, it has been issued by IFSB and AAOIFI, while in Malaysia specifically, it has been provided by Bank Negara Malaysia (BNM) through the Shari’ah Governance Framework 2010 (SGF 2010) and the newly implemented Islamic Financial Service Act 2013 (IFSA 2013). Acknowledging the significant role played by Shari’ah Committee in an IFI’s Shari’ah Governance framework, all of the standards, guidelines and regulations mentioned above provide many provisions with regard to the Shari’ah Committee in order to enhance their role and strengthen their position in the Islamic Finance industry. In this paper, focus will be given on two specific requirements, which are the requirement of qualification background of a Shari’ah Committee and the minimum number of Shari’ah Committee that must be appointed by an IFI. This paper will also discuss the gap between the requirements as provided by AAOIFI, IFSB, SGF 2010 and IFSA 2013, and what is the practice of the IFIs in applying these requirements.